El uso y el cuidado. El sentido de habitar en Una casa llena de gente de Mariana Sández - Szukała, Wiosna (Studia Romanica Posnaniensia, 2024)
This article analyses how the concept of ‘everyday inhabiting’ is problematised in the novel A house full of people (2019) by Mariana Sández. The methodology is based on the philosophy of Giorgio Agamben, especially on two critical categories: use and care, identified by Camilo Boano as components of the definition of inhabiting. In addition, it incorporates Jolanta Brach-Czaina’s theoretical approach to domestic life, highlighting her concept of “everyday hustle and bustle”. The article focuses on ontological and existential considerations, exploring the ethics of daily choices in the way of inhabiting as a key element in the organisation of communal life.